The internal effects of ASEAN external relations - Venzke, Ingo; Thio, Li-ann (Cambridge : Cambridge University Press, 2016)
Starting with a typology of ASEAN external agreements, the authors go on to provide an original reading of plurilateral agreements as'joint' agreements. The book then offers both a clarification of the effects - direct or indirect - of external agreements within the legal orders of ASEAN Member States, and an explanation of the effects of external agreements within the legal regime of ASEAN. The authors conclude with a discussion of the role of ASEAN centrality and the role of the secretariat in shaping it.
Machine generated contents note: 1. Introduction and parameters of inquiry; 2. Contextualizing ASEAN; 3. Types of external agreements; 4. Agreements of ASEAN as an international organization; 5. Plurilateral agreements.
Title from publisher's bibliographic system (viewed on 04 Jul 2016).
Keywords: Law -- Southeast Asia -- International unification; ASEAN; Southeast Asia -- Foreign relations; Southeast Asia -- Politics and government -- 1945-